Developing the "Skippu‐Mama" program for mothers of children with autism spectrum disorder. (4th March 2016) - Niinomi, Kazuteru; Asano, Midori; Kadoma, Akiko; Yoshida, Kumiko; Ohashi, Yukimi; Furuzawa, Ayako; Yamamoto, Mami; Yamakita, Naoko; Mori, Akiko
Abstract: The "Skippu‐Mama" peer support program was developed to improve quality of life and reduce parental stress in mothers of children with autism spectrum disorders. The program was designed to improve these variables by refreshing and healing participants' minds and bodies. Twenty‐four mothers of 26 children diagnosed with ASD in Japan were included in the study and completed measures of quality of life and parental stress before, during, and after participation in the Skippu‐Mama program. Our results demonstrated that time was a significant main effect. Further, multiple comparisons with Bonferroni corrections indicated a significant increase in World Health Organization Quality of Life 26 scores three months into the program and at its conclusion six months after commencement. Overall, the Skippu‐Mama program improved the quality of life of mothers of children with ASD, and we believe that the intervention's focus on both individual and family variables may be especially effective in this population.